The silent sinus syndrome - Mahnaz Sheikhi; Faranak Jalalian (Wolters Kluwer Medknow Publications, 2013)
The silent sinus syndrome (SSS) involves painless facial asymmetry and enophthalmos, which is the result of chronic maxillary sinus atelectasis. In most cases, it is diagnosed clinically, however, using the characteristic imaging features including maxillary sinus outlet obstruction, sinus opacification, and sinus volume loss caused by inward retraction of the sinus walls. Obstruction of the maxillary ostium appears to play a critical role in the development of SSS. Treatment involves functional endoscopic surgery.